How rice adapts to high temperatures - Ren, Huimin; Bao, Jingpei; Gao, Zhenxian; Sun, Daye; Zheng, Shuzhi; Bai, Jiaoteng (Frontiers in Plant Science, 2023)
High-temperature stress affects crop yields worldwide. Identifying thermotolerant crop varieties and understanding the basis for this thermotolerance would have important implications for agriculture, especially in the face of climate change. Rice (Oryza sativa) varieties have evolved protective strategies to acclimate to high temperature, with different thermotolerance levels. In this review, we examine the morphological and molecular effects of heat on rice in different growth stages and plant organs, including roots, stems, leaves and flowers. We also explore the molecular and morphological differences among thermotolerant rice lines. In addition, some strategies are proposed to screen new rice varieties for thermotolerance, which will contribute to the improvement of rice for agricultural production in the future.